PREVALENCE OF DYSLIPIDEMIA AND ITS ASSOCIATION WITH DISEASE ACTIVITY IN PATIENTS WITH RHEUMATOID ARTHRITIS IN SULAIMANI GOVERNORATE - Gharib, Soran Mohammed (Universal Journal of Pharmaceutical Research, 2016)
Objectives: Rheumatoid arthritis is a systemic inflammatory disease characterized by chronic and erosive polyarthritis it is the most common inflammatory arthritis, affecting from 0.5-1% of the general population. Dyslipidemia is a quite important problem in Rheumatoid arthritis (RA) patient, which causes morbidity and mortality. Objectives are to measure prevalence of dyslipidemia in patients with Rheumatoid Arthritis compared with healthy control peoples and to find out correlations between dyslipidemia and disease activity in patients with Rheumatoid Arthritis. Methods: A total of one hundred patients with RA (80 female and 20 male) were included in the study, they were attending consultation clinic and division of rheumatology in the General Medical Teaching Hospital in Slemani city from (October 2015 to September 2016) who fulfilling the 2010 American College of Rheumatology/European league against Rheumatism classification criteria for RA and one hundred healthy age and sex-matched controls. Fasting lipid profiles of cases and control were estimated after an overnight fast of 12 hours. Results: RA patients showed a higher prevalence of associated dyslipidemia (48%) in comparison to control (4%) p- value less than 0.001. Results showed a significant reduction in serum high density lipoproteins (HDL) p-value less than 0.001, with significant elevation of serum total cholesterol, triglyceride, low density lipoprotein and very low density lipoprotein p-value 0.001, 0.007, 0.01and 0.5 respectively in comparison to controls. There is a significant association between dyslipidemia and high DAS 28 score (p=0.02). Conclusion: There is a significant association between high ESR of RA patients and dyslipidemia (p=0.001). A significant association was observed between high CRP level and RA patients with no dyslipidemia (p<0.001). Dyslipidemia are frequent among the patients with rheumatoid arthritis and highly associated with active RA. Serum HDL significantly reduced while other parameters of lipid profiles significantly increased in comparisons to control. Peer Review History: Article received on- 9 October 2016; Revised on- 11 November; Accepted on- 14 December; Available online 15 January 2017 Academic Editor: Dr. Amany Mohamed Alboghdadly , Princess Nourah bint abdulrahman university, Riyadh, amalbgadley@pnu.edu.sa Reviewer(s) detail: Dr. Ahmad Abdelsattar El-Ebiary , Tanta University Hospitals, Tanta, Egypt, a.ebiary@med.tanta.edu.eg Dr. Areen Alshweiat , University of Szeged, Hungary, areen.alshweiat@hu.edu.jo